2009
DOI: 10.1016/j.cemconres.2009.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water-repellent admixtures on the behaviour of aerial lime-based mortars

Abstract: Two different anionic surfactants, sodium oleate and calcium stearate, commercialized as water repellents for cement-based mortars, were added to lime-based mortars in order to check whether they were improved by these admixtures. Different properties of limebased mortars were evaluated: fresh state behaviour through water retention, air content and setting time, hardened state properties such as density, water absorption through capillarity, water vapour permeability, long-term compressive strengths, pore str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 38 publications
5
56
0
13
Order By: Relevance
“…Owing to the increase in small particles when high dosages of additives were used, the mixing water that mortar needed to fulfil the set slump values was larger. In spite of the fact that larger water/binder ratio could lead to a porosity increase, these samples showed no increment in the large pores, as previously reported [29]. It has been found that the rise in mixing water did not involve any drawback regarding the durability behaviour of these mortars, as will be discussed below.…”
Section: Mortars With Water-repelling Agentssupporting
confidence: 70%
See 3 more Smart Citations
“…Owing to the increase in small particles when high dosages of additives were used, the mixing water that mortar needed to fulfil the set slump values was larger. In spite of the fact that larger water/binder ratio could lead to a porosity increase, these samples showed no increment in the large pores, as previously reported [29]. It has been found that the rise in mixing water did not involve any drawback regarding the durability behaviour of these mortars, as will be discussed below.…”
Section: Mortars With Water-repelling Agentssupporting
confidence: 70%
“…In a previous study by our research group [29] mortars with high dosage of sodium oleate showed no sign of deterioration after freezing-thawing cycles. In the present study, the tests carried out on samples with different water repellent dosages showed that when specimens were modified with lower dosages of admixtures, they were destroyed after some cycles ( Fig.…”
Section: Mortars With Water-repelling Agentsmentioning
confidence: 66%
See 2 more Smart Citations
“…Olazagutía, Spain) and a siliceous aggregate were used to prepare the mortars. Material characterization and grain size distribution of the aggregate are reported elsewhere [10].…”
Section: Introductionmentioning
confidence: 99%